FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN DICOFFEE SHOP HOTEL PANGERAN PEKANBARU - ", Hariati; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The performance Achievement of is a process that requires of resources) Thus is performance the level of achievement of the policy, program, activity by using a number of resources in achieving organizational goals that have been set previously. Performance can also be regarded as a work (output) of a process (conversion) perpetrated by all components of the organization of resources (resources) of data and information, policies and time used is referred to as input (input)The purpose of this research was examining the factors that affect the employee performance at the coffee Shop Hotel Pangeran Pekanbaru. The factors tested in this study were the factor leadership, the factor communication, the factor compensation, and the Factor districThe population in this study were staff coffee shop Hotel Pangeran Pekanbaru , while the samples in this study amounted to 58 respondents. The research data was obtained by questionnaire. Techniques used in this study was purposive sampling . The data used are primary and secondary data. The data were analyzed with Importance Performance Analysis.The results of this study indicate variable leadership affect positive signification of employye performance. The Coffee Shop Hotel Pangeran Pekanbaru has factors that affect the performance of is Leadership with sub variables: Leaders clear in giving orders to employees, clever read the situation and sensitive to employees with feedback. And group leaders can create discipline in the workplace. This shows that the role of leader in Departement are essential of purposeKeyword : performance, factor , populasi, and leadership